An analysis of students’ learning difficulties in solving plane geometry problems among seventh-grade students - Andini, Ina; Cahyaningsih, Ujiati (Al-Mufid, 2024)
This study aims to analyze the types and causes of learning difficulties among seventh-grade students in solving problems related to plane geometry. The research specifically focuses on identifying challenges in three major dimensions of mathematical learning: conceptual understanding, application of mathematical principles, and problem-solving skills. A descriptive qualitative method was employed to explore students’ learning behaviors and errors in depth. The participants consisted of three seventh-grade students from SMP Negeri 3 Sungai Ambawang, selected through purposive sampling to represent high, medium, and low academic ability groups. Data were collected through open-ended written tests on plane geometry (covering perimeter, area, and real-life applications of two-dimensional shapes) and semi-structured interviews designed to probe students’ reasoning and sources of error. The collected data were analyzed using Miles and Huberman’s model, which includes data reduction, data display, and conclusion drawing, supported by data triangulation to enhance validity. The results reveal three dominant categories of learning difficulties: (1) conceptual misunderstanding, such as misinterpreting formulas for area and perimeter; (2) procedural inaccuracy, including misapplication of principles and arithmetic errors; and (3) problem-solving challenges, particularly in multi-step reasoning and contextual interpretation. These findings demonstrate that students’ errors are interconnected—conceptual weaknesses often trigger procedural and strategic failures. The study concludes that improving students’ geometry achievement requires integrated instructional strategies emphasizing conceptual clarity, contextualized learning, and guided problem-solving practice. Such approaches can enhance students’ reasoning, visualization, and confidence in mathematics learning.